2023
DOI: 10.3390/dj11060147
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health-Related Quality of Life and Mental Health Impairment in Patients Affected by Medication-Related Osteonecrosis of the Jaws: A Case–Control Pilot Study

Elena Calabria,
Alessandro Antonelli,
Selene Barone
et al.

Abstract: In the present case–control study, the impact of medication-related osteonecrosis of the jaws (MRONJ) on patients’ oral health-related quality of life (OHRQoL), overall quality of life (QoL), and psychological status was evaluated using a set of questionnaires. These questionnaires included the Oral Health Impact Profile-14 (OHIP-14), the Short Form 36 Health Survey Questionnaire (SF-36), and the hospital anxiety and depression scale (HADS). A total of 25 MRONJ patients and 25 controls were included in the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…In the present study, we found that MRONJ was predominantly seen in older individuals (aged ≥ 60 years), with a higher prevalence among females and predominantly affected the mandible aligning with the ndings of Caminha et al 14 The propensity for mandibular involvement is often attributed to its limited end-arterial blood supply and a higher ratio of cortical to cancellous bone. 9 Our ndings revealed that 23.3% of patients presented with stage 1 MRONJ, while 46% had stage 2 MRONJ, consistent with the ndings of Calabria et al, 22 which also showed a higher prevalence of stages 1 and 2 MRONJ.…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, we found that MRONJ was predominantly seen in older individuals (aged ≥ 60 years), with a higher prevalence among females and predominantly affected the mandible aligning with the ndings of Caminha et al 14 The propensity for mandibular involvement is often attributed to its limited end-arterial blood supply and a higher ratio of cortical to cancellous bone. 9 Our ndings revealed that 23.3% of patients presented with stage 1 MRONJ, while 46% had stage 2 MRONJ, consistent with the ndings of Calabria et al, 22 which also showed a higher prevalence of stages 1 and 2 MRONJ.…”
Section: Discussionsupporting
confidence: 89%
“…Subsequent case–control studies are warranted to compare individuals with identical underlying conditions, both with and without MRONJ, in order to elucidate this association. Moreover, standardization of questionnaires for better comparability would be appropriate [ 30 ]. Likewise, the utilization of specific Patient Reported Outcome Measures (PROMs) questionnaires with established psychometric properties would enhance validity, as generic QOL measures may not sufficiently capture mood disturbances [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that localized periodontal or dental disease may precede the onset of MRONJ [23]. Dentists, as part of a multidisciplinary team, have a critical role in preventing MRONJ because the development of this condition can be reduced through prophylactic dental care and the maintenance of good oral hygiene [24][25][26][27]. The importance of prevention is also critical in patients who have to take adalimumab, as this study poses the need to further investigate the association between it and the adverse reaction of MRONJ.…”
Section: Introductionmentioning
confidence: 99%